2015
DOI: 10.5152/akd.2014.5457
|View full text |Cite
|
Sign up to set email alerts
|

Wall motion changes in myocardial infarction in relation to the time elapsed from symptoms until revascularization

Abstract: ObjectiveWall motion abnormalities during acute ST-segment elevation myocardial infarction (STEMI) and the improvement after recanalization depend on the conditions of the coronary occlusion.MethodsFifty-seven patients with first-ever STEMI due to one-artery occlusion, treated with primary PCI, were evaluated. Area at risk and left ventricular wall motion abnormalities were localized with coronary angiography and echocardiography and then compared in relation to the time elapsed from the onset of symptoms at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
3
9
0
2
Order By: Relevance
“…According to the Echocardiographic data, the wall motion (WM) abnormality was detected in all patients (100%) of group A and 75% of group B. the Akinetic segments were around half the patients of group A (53.8%) while were 18.1% in group B. the hypokinetic segments were 36.8% in group A and 65.1% in group B. this is due to the presence and maturity of collaterals and differences in the ischemic tolerance or metabolic characteristics of the myocardium involved [10]. In our study We found in group A that the mean LVESD was 4.3 ± 0.9 cm, the mean LVEDD was 5.4 ± 0.7 cm and the mean EF was 32.3% ± 12.1, whilst in group B we found the mean LVESD was 3.6 ± 0.8 cm, the mean LVEDD was 4.7 ± 0.8 cm and the mean EF was 40.1% ± 9.9.…”
Section: Echocardiographic Data In Ischemic Cardiomyopathymentioning
confidence: 98%
“…According to the Echocardiographic data, the wall motion (WM) abnormality was detected in all patients (100%) of group A and 75% of group B. the Akinetic segments were around half the patients of group A (53.8%) while were 18.1% in group B. the hypokinetic segments were 36.8% in group A and 65.1% in group B. this is due to the presence and maturity of collaterals and differences in the ischemic tolerance or metabolic characteristics of the myocardium involved [10]. In our study We found in group A that the mean LVESD was 4.3 ± 0.9 cm, the mean LVEDD was 5.4 ± 0.7 cm and the mean EF was 32.3% ± 12.1, whilst in group B we found the mean LVESD was 3.6 ± 0.8 cm, the mean LVEDD was 4.7 ± 0.8 cm and the mean EF was 40.1% ± 9.9.…”
Section: Echocardiographic Data In Ischemic Cardiomyopathymentioning
confidence: 98%
“…9,12 Dari segi manajemen penatalaksanaan, waktu antara onset angina dengan pemberian terapi reperfusi merupakan salah satu hal yang penting dalam penanganan pasien IMA, karena jeda waktu tersebut menggambarkan waktu iskemik total, sehingga perlu dikurangi menjadi sesedikit mungkin untuk meningkatkan luaran klinis. [13][14][15] Tindakan PCI sebagian besar mengurangi tingkat disfungsi ventrikel kiri setelah IMA. Meskipun pemulihan ventrikel kiri dimulai sejak awal setelah revaskularisasi, namun waktu optimal untuk penilaian ulang fungsi ventrikel kiri masih belum jelas, tetapi dikatakan bahwa perbaikan gerakan dinding ventrikel kiri biasanya dimulai dalam 3 hari pada pasien yang mengalami revaskularisasi.…”
Section: Diskusiunclassified
“…Meskipun pemulihan ventrikel kiri dimulai sejak awal setelah revaskularisasi, namun waktu optimal untuk penilaian ulang fungsi ventrikel kiri masih belum jelas, tetapi dikatakan bahwa perbaikan gerakan dinding ventrikel kiri biasanya dimulai dalam 3 hari pada pasien yang mengalami revaskularisasi. 1, 15,16 Percutaneous coronary intervention primer adalah strategi reperfusi yang lebih dipilih pada pasien STEMI dalam onset 12 jam jika bisa dilakukan dengan cepat oleh tim yang berpengalaman. Tingkat kematian lebih rendah di antara pasien yang menjalani PCI primer diamati di pusat-pusat dengan volume tinggi prosedur PCI dan didapatkan data penelitian bahwa PCI primer yang dilakukan lebih cepat dan menghasilkan kematian yang lebih rendah jika dilakukan di pusat rujukan PCI.…”
Section: Diskusiunclassified
“…A scarred myocardium will not contract in the same way as the rest of the healthy myocardium (Menon et al 2013). Depending on the severity and thickness of the myocardial injury, the myocardial contractions will be variably affected (Rácz et al 2015). The myocardium can be hypokinetic, defined by less intense myocardial contraction with reduced radial motion but in the normal direction.…”
Section: The Physiology Associated With the Rvpa Conduitmentioning
confidence: 99%